Framework and key considerations for designing and conducting critical mixed-methods research (cMMR) - Younas, Ahtisham; Kvist, Tarja; Stolt, Minna (BMJ Publishing Group, 2026)
Mixed-methods research leverages the strengths of qualitative and quantitative methodologies and methods to generate a comprehensive understanding of phenomena. There is ample guidance about traditional mixed-methods research, but limited discussion on critical mixed-methods research. To provide a conceptual framework and practical considerations for designing and conducting critical mixed-methods research. Contemporary and classical literature in critical research and mixed methods was used to guide the development of this framework. Critical mixed-methods research is informed by critical social theory, critical dialectical pluralism and transformative worldview. The seven core features of critical mixed-methods research are critique, insight, transformation, engagement, epistemic inclusion, critical reflexivity and intersectionality. Critical mixed methods is necessary and needed for studying social justice and equity-related research problems in health sciences and public health. Using the proposed framework and practical strategies can enable researchers to unravel complex social and healthcare phenomena through addressing power, oppression and social justice issues.